2021
DOI: 10.1515/tjb-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum 25 hydroxyvitamin D deficiency on lipid biomarkers in established coronary artery disease

Abstract: Objectives Vitamin D deficiency (VDD) is associated with coronary artery disease (CAD) directly by augmenting atherosclerosis and indirectly through cardiovascular risk factors. The present study was aimed to find an association of 25 hydroxyvitamin D (25(OH)D) with lipid profile among established CAD. Methods A cross-sectional study was conducted among 73 patients of angiographically confirmed CAD aged between 35 and 55 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Vitamin D may also prevent cardiovascular disease by regulating several genes involved in cell differentiation, proliferation, apoptosis, and angiogenesis [72]. In fact, another proposed mechanism for the protective effect of vitamin D on CVD is the control of lipid parameters [11,12,33,[73][74][75][76] In the present study, lipid profile assessment revealed dyslipidemia in 33.3% of all participants. Non-parametric regression showed that 25(OH)D concentration was inversely associated with TC, TG, and LDL-C levels and positively associated with HDL-C.…”
Section: Discussionmentioning
confidence: 60%
“…Vitamin D may also prevent cardiovascular disease by regulating several genes involved in cell differentiation, proliferation, apoptosis, and angiogenesis [72]. In fact, another proposed mechanism for the protective effect of vitamin D on CVD is the control of lipid parameters [11,12,33,[73][74][75][76] In the present study, lipid profile assessment revealed dyslipidemia in 33.3% of all participants. Non-parametric regression showed that 25(OH)D concentration was inversely associated with TC, TG, and LDL-C levels and positively associated with HDL-C.…”
Section: Discussionmentioning
confidence: 60%